Are the Clinical outcomes of Neonates and Infants Under 2 Months Old with Urinary Tract Infections Similar to those in Infants 2 to 12 Months Old? - Jee Hoo Lee; Hyunwook Lim; Kyungju Kim; Hyung Eun Yim; Kee Hwan Yoo (Childhood Kidney Diseases, 2015)
Purpose: Although the American Academy of Pediatrics provides clinical guidelines for urinary tract infection (UTI) infants, guidelines are not appropriate for neonates and infants less than 2 months of age due to insufficient data. The aim of this study was to evaluate the characteristics of neonates and young infants less than 2 months old (group 1) with UTI compared to older infants from 2 to 12 months old (group 2). Methods: We reviewed UTI patients aged 0 to 12 months admitted to the pediatric department in the last 5 years. Clinical characteristics such as age, sex, fever duration, recurrence, progression to acute pyelonephritis (APN), malformations like hydronephrosis and vesicoureteral reflux (VUR), and laboratory results were compared between group 1 and group 2. Results: 615 patients were included in this study. Group 1 had 94 cases and group 2 had 521 cases. Escherichia coli was the most commonly isolated pathogen in urine cultures. Fever duration was shorter in group 1 (vs.) 2 (1.91±1.43 days vs. 3.42±2.40 days, P<0.05). As compared to group 2, group 1 had a higher proportion of patients with antenatal hydronephrosis and hydronephrosis found after admission (10.6% vs. 3.6% and 75.5% vs. 55.9%, P<0.05). There were differences between two groups in white blood cell (WBC) count (Group 1: 13,694±5,315/μL, Group 2: 15,271±6,130/μL, P<0.05) and C-reactive protein (Group 1: 32.02±35.17 mg/L, Group 2: 46.51±46.63 mg/L, P<0.05). Conclusion: Compared to older infants, UTI in neonates and young infants shows milder clinical manifestations except higher rates of hydronephrosis but outcome is alike.